2020
DOI: 10.3390/vetsci7010031
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of a Phage Mixture and a Lactic Acid Bacterium against Staphylococcus aureus from Bovine Mastitis

Abstract: The antimicrobial activity of a phage mixture and a lactic acid bacterium against Staphylococcus aureus isolates from bovine origin was investigated in vitro with regard to possible applications in the therapy of udder inflammation (mastitis) caused by bacterial infections. The S. aureus isolates used for inoculation derived from quarter foremilk samples of mastitis cases. For the examination of the antimicrobial activity, the reduction of the S. aureus germ density was determined [log10 cfu/mL]. The phage mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 57 publications
(93 reference statements)
0
18
0
3
Order By: Relevance
“…Both in vitro and in vivo studies have shown the effectiveness of bacteriophage-based therapy in the reduction of Staphylococcus aureus bacteria that causes mastitis in cattle [ 97 , 98 ]. However, in the case of pigs, Verstappen et al [ 49 ] showed, in in-vitro and in-vivo assays, no inhibition of nasal colonization by MRSA strains with the use of specific phages.…”
Section: Bacteriophagesmentioning
confidence: 99%
“…Both in vitro and in vivo studies have shown the effectiveness of bacteriophage-based therapy in the reduction of Staphylococcus aureus bacteria that causes mastitis in cattle [ 97 , 98 ]. However, in the case of pigs, Verstappen et al [ 49 ] showed, in in-vitro and in-vivo assays, no inhibition of nasal colonization by MRSA strains with the use of specific phages.…”
Section: Bacteriophagesmentioning
confidence: 99%
“…Recently, more studies on phage therapy for mastitis in cattle have been developed with positive, significant results using phage cocktails in mouse models. They have shown a decrease in the number of colony-forming units and a significant improvement in mastitis pathology, even greater than in mice treated with a single phage [ 55 , 73 ].…”
Section: Phage Therapy In the Veterinary Fieldmentioning
confidence: 99%
“…MIC of lacticin A164 and lacticin BH5 needed to inhibit the growth of H. pylori ATCC 43504 was 12.5 mg l À1 . 108…”
Section: Lacticinmentioning
confidence: 99%